2012
DOI: 10.1098/rsbl.2012.0137
|View full text |Cite
|
Sign up to set email alerts
|

A test of the oxidative damage hypothesis for discontinuous gas exchange in the locust Locusta migratoria

Abstract: The discontinuous gas exchange cycle (DGC) is a breathing pattern displayed by many insects, characterized by periodic breath-holding and intermittently low tracheal O 2 levels. It has been hypothesized that the adaptive value of DGCs is to reduce oxidative damage, with low tracheal O 2 partial pressures (PO 2 ∼2-5 kPa) occurring to reduce the production of oxygen free radicals. If this is so, insects displaying DGCs should continue to actively defend a low tracheal PO 2 even when breathing higher than atmosph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 14 publications
1
24
0
1
Order By: Relevance
“…This may indicate an overall insensitivity of the species to oxygen variation, which may be of further interest itself in light of the oxidative damage hypothesis of DGE (e.g. Hetz and Bradley, 2005;Boardman et al, 2012;Matthews et al, 2012).…”
Section: Comparing Methods For Partitioning Water Lossmentioning
confidence: 99%
“…This may indicate an overall insensitivity of the species to oxygen variation, which may be of further interest itself in light of the oxidative damage hypothesis of DGE (e.g. Hetz and Bradley, 2005;Boardman et al, 2012;Matthews et al, 2012).…”
Section: Comparing Methods For Partitioning Water Lossmentioning
confidence: 99%
“…Furthermore. Matthews et al [30 ] used fiber-optic oxygen optodes to observe tracheal PO 2 in locusts and found that locusts maintained a low tracheal PO 2 near 3.4-1.4 kPa in normoxic or hypoxic (10% O 2 ) conditions. However, when placed in hyperoxic environments, these insects did not maintain a PO 2 any lower than 30 kPa, therefore challenging the idea that tracheal hypoxia is beneficial in hyperoxic environments.…”
Section: Oxidative Damage Hypothesismentioning
confidence: 99%
“…Recent experimental and comparative studies have lent their support to the hygric and oxidative‐damage hypotheses (Hetz & Bradley, ; Marais et al ., ; White et al ., ; Terblanche et al ., ; Schimpf et al ., , ; Williams et al ., ; Matthews & White, ). Others, on the other hand, have yielded results to the contrary (Contreras & Bradley, ; Boardman et al ., ; Matthews et al ., ), and no hypothesis enjoys unopposed support.…”
Section: Introductionmentioning
confidence: 97%